Killer summer - Pearson, Ridley (New York : G.P. Putnam's Sons, 2009)
Sun Valley sheriff Walt Fleming returns in this high- intensity thriller as he thwarts a plan to steal a rare wine at the annual wine auction. When a bomb detonates just as the auction revs up, the investigation explodes as well, pulling Walt in a dozen different directions.
Keywords: Sheriffs -- Idaho -- Fiction; Wine auctions -- Fiction; Theft -- Fiction; Sun Valley (Idaho) -- Fiction; Suspense fiction